Innowacyjność Polski w warunkach członkostwa w Unii Europejskiej - Puślecki, Zdzisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The implementation of the European Union's new competitive and innovation policy in Poland should, in practice, mean the efforts that result from the current methods and tools of the above mentioned policies, and which also take into account national priorities in the scientific, technological or regional policies, but which, at the same time, are compatible with those that are being currently employed in the European Union. If, however, Poland rejects the Union path, it will be impossible for this country to participate in the framework programmes, and in other forms of financial aid, which would mean suspending the reforms of the R&D sector, of the system for financing research and development of innovative entrepreneurship. Yet, a membership fee is obligatory, regardless how much the member state benefits from the EU financial aid. If, however, a country accepts the challenge of carrying out a strategy based on strengthening the innovation factors of development, it will be able to gradually increase the profits resulting from the participation in the European research and innovation area, and to close up slowly the technological gap. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 307-316